Can I Choose a Throwable Object for You? Perceiving Affordances for Other Individuals - Ji, Huichao; Pan, Jing Samantha (Frontiers in Psychology, 2019)
Throwing is an important motor skill for human survival and societal development. It has been shown that throwers could select throwable balls for themselves and ball throwability was determined by its size and weight. In this study, we investigated whether throwers could perceive ball throwability for other throwers (experimental confederates) and whether the perceived throwability for others also followed a size-weight relation. Like other types of affordances, throwability entails a scaling between the thrower and the throwing object. This requires knowledge about the thrower and the object. In this study, knowledge about the objects was gained by hefting balls of various sizes and weights; knowledge about the throwers was gained by interacting with throwers in person (Experiment 1) and by viewing videos of confederates throwing (containing kinematic and anthropometric information) or photographs of the confederates standing (containing anthropometric information; Experiment 2). By comparing observers’ perceived throwability for others using various materials, we attempted to uncover whether scaling of throwability was based on kinematic or anthropometric information. In this study, participants ranked throwability of balls of various sizes and weights for confederates of different sexes and fitness levels. In all experimental conditions, observers’ ranking and confederates’ actual throwing performances yielded linear relationships with slopes close to 1 and moderate to high r2 values. These suggested that participants were able to accurately perceive throwability and choose throwable balls for the confederates. The throwable balls followed a size-weight relation, where bigger balls had to weigh more to be perceived as throwable as smaller balls. Furthermore, there was no difference between throwability perception based on in-person interaction, watching videos of confederates throwing and seeing pictures of the confederates standing. This suggested that the scaling of throwability was likely to be based on anthropometric information. These results enriched our understanding of whether one could perceive the action opportunities for others, and extended the canonical Gibsonian concept of affordance to a social setting and thus could be important for understanding team coordination in sports and interpersonal action collaboration in general.